2019
DOI: 10.1039/c9ta01752f
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale computational assembly of ionic liquid/MOF composites: synergistic effect in the wire-tube conformation for efficient CO2/CH4 separation

Abstract: High-throughput construction of IL/MOF composites and discovery of the synergistic effect in the wire-tube conformation for efficient CO2/CH4 separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 51 publications
2
57
0
Order By: Relevance
“…Expanding upon these previous reports, this study applies ML to explore a large database of 918,734 known and proposed MOFs. The database was assembled from a diverse collection of publicly available MOF repositories, 1 , 29 , 31 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 81 , 82 and allows for a wide-ranging and consistent assessment of H 2 uptake in MOFs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expanding upon these previous reports, this study applies ML to explore a large database of 918,734 known and proposed MOFs. The database was assembled from a diverse collection of publicly available MOF repositories, 1 , 29 , 31 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 81 , 82 and allows for a wide-ranging and consistent assessment of H 2 uptake in MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…A database of crystal structures for 918,734 MOFs was created by combining 19 existing databases. 1 , 29 , 31 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 81 , 82 Table 2 summarizes the source databases and the number of MOFs contained in each. Out of these 19 databases, only the UM, 31 CSD, 29 , 30 and CoRE 33 , 34 databases contain data on MOFs that have been previously synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…With the ratio of CO 2 /CH 4 in mixture at 50:50, the adsorption on MOFs was simulated with GCMC method at 298 K and 1 bar using the same method as in Xe/Kr. Note that the best separation material in the G-MOFs database is Zn 2 O 8 -BTC_B-irmof7_A_No16, 26 corresponding to the selectivity of CO 2 /CH 4 at 50.5 and uptake of CO 2 at 4.0 mmol/g, which is lower than SAJFEO with the CO 2 /CH 4 selectivity at 210.33 and uptake of CO 2 at 6.31 mmol/g. 55 Through the data analysis as listed in Table S3 , we found that the calculated adsorption properties in G-MOFs datasets are obviously imbalanced, especially for the adsorption selectivity of CO 2 /CH 4 .…”
Section: Results and Discussionmentioning
confidence: 98%
“… 26 To date, 162 thoroughly different MOF structures have been synthesized experimentally in G-MOFs. 26 …”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation